The Role of Artificial Intelligence in Improving Project Management Processes: An Applied Study on the Information Technology Sector in the Kingdom of Saudi Arabia (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2024)
This study analyzes the significant role of AI in enhancing project management processes within the IT sector in Saudi Arabia. As the digital landscape continues to grow, the integration of AI technology has emerged as an important aspect in improving efficiency, accuracy, and creativity in project management techniques. The research uses a quantitative approach, using a structured questionnaire conducted on a sample of 135 IT professionals. These individuals were selected to share their insights about their experiences and perspectives on deploying AI in their project management activities. The data obtained from the surveys was subjected to rigorous statistical analysis to measure the impact of AI on several dimensions of project management. The results show that AI plays a significant role in reducing human errors, thereby enhancing the overall quality of project deliverables. By automating repetitive processes and leveraging predictive analytics, AI reduces the chance of errors that may arise from manual procedures, resulting in more reliable project deliverables. By reducing communication channels, AI creates a more unified work environment, enabling teams to respond quickly to obstacles and adapt to changing project needs. This study highlights the revolutionary potential of AI in the IT industry in Saudi Arabia, and its critical role in transforming project management processes. The findings provide important insights for industry practitioners and decision makers, supporting the deployment of AI technology to achieve operational excellence and enhance innovation. By understanding and harnessing the benefits of AI, companies may enhance their project management capabilities, ultimately leading to superior project outcomes and a sustainable competitive advantage in a rapidly changing technology world.